Two novel type II receptors mediate BMP signalling and are required to establish left-right asymmetry in zebrafish. - Monteiro, R; van Dinther, M; Bakkers, J; Wilkinson, R; Patient, R; ten Dijke, P; Mummery, C (2008)
Ligands of the transforming growth factor beta (TGFbeta) superfamily, like Nodal and bone morphogenetic protein (BMP), are pivotal to establish left-right (LR) asymmetry in vertebrates. However, the receptors mediating this process are unknown. Here we identified two new type II receptors for BMPs in zebrafish termed bmpr2a and bmpr2b that induce a classical Smad1/5/8 response to BMP binding. Morpholino-mediated knockdown of bmpr2a and bmpr2b showed that they are required for the establishment of concomitant cardiac and visceral LR asymmetry. Expression of early laterality markers in morphants indicated that bmpr2a and bmpr2b act upstream of pitx2 and the nodal-related southpaw (spaw), which are expressed asymmetrically in the lateral plate mesoderm (LPM), and subsequently regulate lefty2 and bmp4 in the left heart field. We demonstrated that bmpr2a is required for lefty1 expression in the midline at early segmentation while bmpr2a/bmpr2b heteromers mediate left-sided spaw expression in the LPM. We propose a mechanism whereby this differential interpretation of BMP signalling through bmpr2a and bmpr2b is essential for the establishment of LR asymmetry in the zebrafish embryo.